Pattern recognition using artificial neural network / Abdul Jalil Hussin - Hussin, Abdul Jalil (1992)
The purpose of this project is to develop an organizing discipline by which neural network system can be design for specific computations. Furthermore, it is also to recognize and make use of both the similarities and differences between well-established procedures and the newly proposed neural approaches.